Central congenital diaphragmatic hernia with cardiac compression in a neonate - Rachel F. Thompson; James Davis (Elsevier, 2022)
Congenital diaphragmatic hernias (CDH) occur when the diaphragm fails to close during normal fetal development. The most common subtypes are Bochdalek and Morgagni hernias. There are a variety of presentations from asymptomatic to severe cardiopulmonary compromise present at birth. Presented is a case of a six-day-old neonate with a postero-central diaphragmatic hernia with herniated liver causing right atrial compression and right-to-left shunting across the patient's patent foramen ovale (PFO). The hernia was repaired with a laparoscopic patch technique.